Air Regeneration of a Silicalite Column Loaded with Ethanol: Modelling and Energy Estimation - José A. Delgado; Vicente I. Agueda; María A. Uguina; José L. Sotelo; Alvaro García; Alicia García-Sanz (Adsorption Science & Technology)
Concentration-thermal swing adsorption (CTSA) using an ethanol-selective adsorbent can be an attractive option to reduce the energy costs associated with the separation of ethanol from water. In this process, ethanol regeneration is the only step with significant energy consumption, in which the adsorbent column saturated with liquid ethanol is purged with a hot inert gas to recover ethanol by condensation. Despite many showing interest in applying CTSA, the method has received little attention in the open literature, and consequently little information is available about its energy requirement. In this work, we experimentally measured the regeneration dynamics of a heated silicalite column saturated with liquid ethanol by air purge using different column wall temperatures and purge gas flow rates. Using a theoretical model based on conservation equations, the mass and heat transfer kinetics in this process are adequately reproduced. The proposed model has been used to estimate the overall energy requirement of the ethanol vapourization/desorption and the subsequent condensation processes.